Hybrid multiphoton and optoacoustic microscope - Tserevelakis, George J.; Soliman, Dominik; Omar, Murad; Ntziachristos, Vasilis (Optics Letters, 2014)
We present a hybrid microscope combining multiphoton microscopy incorporating second-harmonic generation contrast and optical-resolution optoacoustic (photoacoustic) microscopy. We study the relative performance of the two systems and investigate the complementarity of contrast by demonstrating the label-free imaging capabilities of the hybrid microscope on zebrafish larvae ex vivo, concurrently visualizing the fish musculature and melanocytes. This implementation can prove useful in multiparametric microscopy studies, enabling broader information to be collected from biological specimens. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08